Plasmodium Impairs Antibacterial Innate Immunity to Systemic Infections in Part Through Hemozoin-Bound Bioactive Molecules - Harding, Christopher L.; Villarino, Nicolas F.; Valente, Elena; Schwarzer, Evelin; Schmidt, Nathan W. (Frontiers in Cellular and Infection Microbiology, 2020)
One complication of malaria is increased susceptibility to invasive bacterial infections. Plasmodium infections impair host immunity to non-Typhoid Salmonella (NTS) through heme-oxygenase I (HO-I)-induced release of immature granulocytes and myeloid cell-derived IL-10. Yet, it is not known if these mechanisms are specific to NTS. We show here, that Plasmodium yoelii 17XNL (Py) infected mice had impaired clearance of systemic Listeria monocytogenes (Lm) during both acute parasitemia and up to 2 months after clearance of Py infected red blood cells that was independent of HO-I and IL-10. Py-infected mice were also susceptible to Streptococcus pneumoniae (Sp) bacteremia, a common malaria-bacteria co-infection, with higher blood and spleen bacterial burdens and decreased survival compared to naïve mice. Mechanistically, impaired immunity to Sp was independent of HO-I, but was dependent on Py-induced IL-10. Splenic phagocytes from Py infected mice exhibit an impaired ability to restrict growth of intracellular Lm, and neutrophils from Py-infected mice produce less reactive oxygen species (ROS) in response to Lm or Sp. Analysis also identified a defect in a serum component in Py-infected mice that contributes to reduced production of ROS in response to Sp. Finally, treating naïve mice with Plasmodium-derived hemozoin containing naturally bound bioactive molecules, excluding DNA, impaired clearance of Lm. Collectively, we have demonstrated that Plasmodium infection impairs host immunity to diverse bacteria, including S. pneumoniae, through multiple effects on innate immunity, and that a parasite-specific factor (Hz+bound bioactive molecules) directly contributes to Plasmodium-induced suppression of antibacterial innate immunity.